Quality of Life in Parkinson's Disease Caregivers: The Contribution of Personality Traits - Tew, Eloise H. (Hindawi Publishing Corporation, 2013)
Parkinson's disease imposes significant demands not only on patients but also on those people living and caring for them, who often have a reduction in their quality of life. The factors that may ameliorate these effects, such as an individual's personality, are not understood. Therefore, the aim of this study was to look at the relative contribution of caregiver personality on their quality of life, specifically attempting to identify those traits, which may be protective or harmful. Two hundred and seventy-four caregivers of patients with Parkinson's disease were included in this study. Caregivers were given questionnaires to complete, including the Big Five Inventory and the World Health Organisation Quality of Life BREF version. Univariate correlations demonstrated that depression and anxiety were the largest predictors of reduced quality of life amongst caregivers. However, after controlling for these potential confounds, conscientiousness was associated with enhanced psychological quality of life and openness positively predicted benefits in the environmental domain. Neuroticism was associated with reduced quality of life in the psychological domain. Thus, screening for neuroticism may help identify those caregivers who would benefit from intervention strategies, which could in the long term help reduce the need for nursing home placement of Parkinson's disease patients.